(untitled) (AYUSHDHARA, 2023)
The fast evolving present era is not only upfront in case of technological developments but also been in top for the manifestation of lifestyle disorders. The origin of almost all the diseases start basically from the food habits itself. The alterations in the gastro - intestinal system will later lead to the development of wide spectrum of diseases. Irritable Bowel Syndrome (IBS) is one of the common gastrointestinal functional disorders that affects millions of people worldwide. IBS is characterised by a complex group of symptoms including abdominal pain or bloating, diarrhoea and constipation, which can affect the quality of life of an individual. The symptomatologies explained in IBS had been explained under a spectrum of diseases called Grahani. Grahani, according to Ayurvedic classics, is caused by the imbalance of Agni or digestive fire, which leads to the imbalance in the digestion metabolism. Grahani can be effectively treated through the combination of dietary and life style modifications along with Ayurvedic medicines and therapies. The treatment aims nothing but to balance the digestive fire as well as to remove toxins from the body in order to restore proper digestion as well as overall health. Takra basti is known to have a very good efficacy in the management of Grahani roga. A successfully treated Grahani case using Takra basti and Shamana oushadhi’s will be discussed in this article.